The roles of a university in sustaining telecentre implementation: The case of Kg. Oran, Perlis - Ibrahim, Huda (Universiti Utara Malaysia, 2012)
This report is based on a case study of a typical rural village in Malaysia, Kampong Oran in Perlis, with the aim to present and propose numerous roles that can be effectively deployed by institutions of higher learning to the rural areas as part of the initiative to bridge the digital divide. This effort can also be seen as a social responsibility coming from academic institutions in extending their knowledge and expertise to reach the under served communities in the rural and remote areas of the country, in line with the government’s Rural Transformation Program that was launched recently.The idea is to bring the experts and knowledgeable people as well as students in numerous disciplines to be within reach of the less educated, largely poor and less fortunate community using information, communication and technology as a platform.The advent of ICT and pervasiveness of the internet has made it possible for rural communities, including Kampong Oran, to reap the benefits of the information explosion. This is made possible through the implementation of a telecentre within the vicinity of a local mosque, a place of worship and congregations of the largely Malay community in the area.However, despite the ICT access and opportunity to gain information, due to over-abundance of information readily available, it is difficult to fine-tune and focus those information that are of interest to the community. This has made the tasks of getting the IHL support to match against the interests of the community even harder. Therefore the case study in which this report is based on was conducted to identify the community requirements in their implementation of the telecentre, to identify the roles of the IHL in order to make the matching possible, and ultimately to propose a model of IHL collaboration vis-à-vis implementation of the telecentre. Methods of data gathering included the administration of questionnaires in the form of surveys to members of the community by means of a purposive sampling in a community gathering event commemorating an ICT Open Day.Apart from this, interviews were also conducted to members of the village management committee, mosque community, and selected individuals representing members of the community. Students were also deployed to assist the researchers as informants and formed part of their course project.The purpose is to identify the community profile and demography, ICT knowledge and skills, requirements of the telecentre, as well as the community’s information needs. On the roles of the IHL, series of brainstorming sessions were conducted amongst the members of the research team, ITU-UUM officials and fellows to identify the strengths and domain areas of UUM.The intention is to propose the types of info-mediation, content development, and value creation that can be applied to benefit the community of Kampong Oran based on their information needs. In terms of information needs, results of this study found that the top five most popular information needs identified by the community are Education, Healthcare, Current News/Sports, Religion, and Information Sources.A model of IHL Collaboration in Telecentre Implementation was created to represent the interplay between the roles of the IHLs and the community information needs through the implementation of the telecentre.It is the hope that this model would contribute to other similar rural communities in the country that is in need of intellectual engagement in terms of advisory services, local content development, and socio-economic value creation that would enable ever-lasting sustainability of their existing telecentre.